DERMINEUR, Elise M. (2025), Before Banks: The Making of Credit and Debt in Preindustrial France, Cambridge, Cambridge University Press. ISBN 9781009502641, 293 pp. - Rodrigues, Lisbeth (História: revista da Faculdade de Letras da Universidade do Porto, 2026)